2020
DOI: 10.3390/toxins12090585
|View full text |Cite
|
Sign up to set email alerts
|

[D-Leu1]MC-LR and MC-LR: A Small–Large Difference: Significantly Different Effects on Phaseolus vulgaris L. (Fabaceae) Growth and Phototropic Response after Single Contact during Imbibition with Each of These Microcystin Variants

Abstract: [D-Leu1]MC-LR and MC-LR, two microcystins differing in one amino acid, constitute a sanitary and environmental problem owing to their frequent and concomitant presence in water bodies of the Americas and their association with human intoxication during recreational exposure to cyanobacterial bloom. Present in reservoirs used for irrigation as well, they can generate problems in the development of crops such as Phaseolus vulgaris, of nutritional and economic interest to the region. Although numerous works addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Small variations in the chemical structure of MCs were shown recently to have a significant impact on phytotoxicity. The variant (D-Leu1) MC-LR, found, for example, in La Plata Basin blooms in Argentina, proved to be more toxic than MC-LR to common bean ( Phaseolus vulgaris L.) [ 27 ]. Malaissi et al (2020) [ 27 ] reported the inhibition of germination after a single contact in the imbibition stage and delay in the development of common bean seedlings.…”
Section: Plant Responses Related To Toxin Concentration and Chemical Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Small variations in the chemical structure of MCs were shown recently to have a significant impact on phytotoxicity. The variant (D-Leu1) MC-LR, found, for example, in La Plata Basin blooms in Argentina, proved to be more toxic than MC-LR to common bean ( Phaseolus vulgaris L.) [ 27 ]. Malaissi et al (2020) [ 27 ] reported the inhibition of germination after a single contact in the imbibition stage and delay in the development of common bean seedlings.…”
Section: Plant Responses Related To Toxin Concentration and Chemical Structurementioning
confidence: 99%
“…The variant (D-Leu1) MC-LR, found, for example, in La Plata Basin blooms in Argentina, proved to be more toxic than MC-LR to common bean ( Phaseolus vulgaris L.) [ 27 ]. Malaissi et al (2020) [ 27 ] reported the inhibition of germination after a single contact in the imbibition stage and delay in the development of common bean seedlings. Alterations in the structure of the leaves (alteration in the size, color and shape), roots (smaller root area) and stems (shorter stem lengths), as well as alterations in leaf stomatal density and conductivity were also reported ( Table 1 ).…”
Section: Plant Responses Related To Toxin Concentration and Chemical Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Some fairly rare toxins may abound locally and may represent important hazards that affect people, animals, and even crops. Anabaenopeptins (A, B, C, and F) and Oscilamide Y were detected at unusually high concentrations in a reservoir system in NE Spain [ 11 ] and [D-Leu 1 ]MC-LR is more frequent than MC-LR in some South American countries [ 12 ]. The detection of some of these compounds may pose a challenge, and Flores and Caixach [ 11 ] recommend taking a suspect screening approach based on High-Resolution Mass Spectrometry (HRMS) for the cyanobacterial peptides that are not often monitored by target strategies.…”
mentioning
confidence: 99%
“…[D-Leu1] MC-LR is frequently reported in water bodies throughout America and shows clear toxic potency differences with MC-LR, with greater phosphatase activity inhibition in both animal and plant models. The effects on plants ( Phaseolus vulgaris ) can be observed from germination at fairly low concentrations [ 12 , 13 ]. This may be a warning for not only managers to be aware of most minority compounds that challenge the accuracy of methods, but also for researchers to study the potential toxic effects of Anabaenopeptins and Oscilamide, among others.…”
mentioning
confidence: 99%